2014
DOI: 10.14784/jfrs.2014117327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Investor Sentiment on Stock Markets

Abstract: Motivation of this study is to examine the relationship between investor sentiment and stock market by taking financial crisis period into account. When literature is examined, it is seen that there is a deficiency in this respect. Although there are studies examining same phenomena, none of them has considered the impact of financial crisis. To eliminate this deficiency, we have employed tests with structural breaks rather than conventional ones. At the end of these tests, structural breaks are observed at cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In contrast research [22], [23] stated no relationship between trading volume and returns on stock indices on the stock market. In addition, research [24,25] suggests an influence between consumer confidence and stock prices. In contrast to research [26], it states that the relationship between consumer confidence and stock prices is counterintuitive.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast research [22], [23] stated no relationship between trading volume and returns on stock indices on the stock market. In addition, research [24,25] suggests an influence between consumer confidence and stock prices. In contrast to research [26], it states that the relationship between consumer confidence and stock prices is counterintuitive.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Topuz (2011), using Granger causality analysis for the period 2004-2009, the causality relationship between the BIST 100 index and CCI was examined, and as a result of the analysis, it was determined that there was a unidirectional causality from stocks to consumer confidence index. In a study conducted by Bolaman and Evrim Mandacı (2014), they examined the relationship between NDI and stock returns for the 2003-2012 period using the Gregory-Hansen cointegration test and stated that there is a long-term relationship between the two variables because of the study.…”
Section: Consumer Confidence Indexmentioning
confidence: 99%
“…One of the factors which plays a significant role in the stock market is the confidence of investors or investor’s sentiments towards the stock market in the economy. Investor sentiment index in equity is found to affect the stock returns positively in the market (Anusakumar et al, 2017; Bolaman & Mandaci, 2014; Oprea & Brad, 2014). However, some studies has also shown a negative relationship between the two (Schmeling, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chang et al (2009) in their semantic paper have examined and found a significant role of individual investor sentiment index in predicting the stock returns in developed as well as developing countries. Bolaman and Mandaci (2014) have studied and found a positive long-term relationship between investors’ sentiments and Turkish stock market while taking financial crisis period into account. Anusakumar et al (2017) have worked on the sentiments of investors and its impact on the equity stock returns by categorizing the sentiments as stock-specific and market-specific.…”
Section: Literature Reviewmentioning
confidence: 99%